Influence of the Implementation and use of Information Systems Accounting for the Quality of Financial Reports Dompu Regional General Hospital - Lala Faradila; Bambang (Formosa Journal of Multidisciplinary Research, 2024)
The aim of this research is to understand how the quality of the Dompu Regional General Hospital's financial reports is influenced by the implementation and use of accounting information systems. The population in this study was the staff or financial administration section of the Dompu Regional General Hospital, with a non-probability sampling technique, namely all members of the population totaling 33 respondents were taken as samples. Quantitative methods are used in research by collecting data using questionnaires measured using a Likert scale. The results of this research show that the implementation and use of an accounting information system has a positive and significant effect on the quality of the financial reports of the Dompu Regional General Hospital.